2024
DOI: 10.1111/nph.19504
|View full text |Cite
|
Sign up to set email alerts
|

Rapid in situ diversification rates in Rhamnaceae explain the parallel evolution of high diversity in temperate biomes from global to local scales

Qin Tian,
Gregory W. Stull,
Jürgen Kellermann
et al.

Abstract: Summary The macroevolutionary processes that have shaped biodiversity across the temperate realm remain poorly understood and may have resulted from evolutionary dynamics related to diversification rates, dispersal rates, and colonization times, closely coupled with Cenozoic climate change. We integrated phylogenomic, environmental ordination, and macroevolutionary analyses for the cosmopolitan angiosperm family Rhamnaceae to disentangle the evolutionary processes that have contributed to high species diversit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 99 publications
(143 reference statements)
0
4
0
Order By: Relevance
“…It is pervasive for species to retain the climatical preferences of their ancestors [ 18 , 19 ]. An increasing number of studies have found that niche conservatism play a major role in shaping various distribution patterns, including LDGs [ 15 , 58 ], inverse LDGs [ 3 , 5 , 8 , 10 ], and others [ 59 , 60 ]. However, the influence of evolutionary time and diversification rates on driving species distribution patterns varies greatly across lineages, regardless of whether these distribution patterns conform to LDGs or inverse LDGs [ 3 , 6 , 9 , 10 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is pervasive for species to retain the climatical preferences of their ancestors [ 18 , 19 ]. An increasing number of studies have found that niche conservatism play a major role in shaping various distribution patterns, including LDGs [ 15 , 58 ], inverse LDGs [ 3 , 5 , 8 , 10 ], and others [ 59 , 60 ]. However, the influence of evolutionary time and diversification rates on driving species distribution patterns varies greatly across lineages, regardless of whether these distribution patterns conform to LDGs or inverse LDGs [ 3 , 6 , 9 , 10 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of studies have found that niche conservatism play a major role in shaping various distribution patterns, including LDGs [ 15 , 58 ], inverse LDGs [ 3 , 5 , 8 , 10 ], and others [ 59 , 60 ]. However, the influence of evolutionary time and diversification rates on driving species distribution patterns varies greatly across lineages, regardless of whether these distribution patterns conform to LDGs or inverse LDGs [ 3 , 6 , 9 , 10 , 12 ]. Generally, the lineages with ancient origins tend to favor the time-for-speciation hypothesis, such as Cycadaceae (stem age: ca.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations